The Usage of Micro Modular Nuclear Reactors on Military Headquarters as a Prospective Solution to Achieve Energy Security and Improve National Defense - Samuel Yohenson Yoce Matthews; Yanif Dwi Kuntjoro; Purnomo Yusgiantoro (PT FORMOSA CENDEKIA GLOBAL, 2023)
Recently, there has been a trend of developing Micro Modular Reactors in the Small Nuclear Reactor field that can produce up to 15 MW(e) of power. Micro Modular Reactor is the fourth-generation technology which is included in the sub-category of Small Modular Reactor or Small Modular Reactor. This reactor produces electricity and heat that is safe, clean and economical which is believed to be better than large-scale Nuclear Power Plants. Micro-reactors have several technological advantages in that they can be manufactured in a factory setting, transported and assembled more easily, and can be integrated with renewable micro-power grids. Through the literature study method, this research analyzes the prospect of using Micro Modular Reactor technology for military headquarters in order to support national defense. The results of the analysis of this study conclude that MMR technology is worth trying to be applied in Indonesia, especially for electricity generation in state institutions, but it is necessary to carry out a further feasibility analysis of the possibility of state losses as a form of the ideas put forward in this study.